A Systematic Literature Review of Digital Transformation - Sarmiento, Allen Grace M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The introduction of information, technology, and innovation in goods and services is the cornerstone of success in the modern global economy. These significant digital revolution shifts have established new digitally related practices that enhance and add value to the way businesses and organizations operate. With this, it is more crucial than ever to comprehend the potential benefits digital transformation projects may offer businesses and the economy. This study contributes to the continuous research related to digital transformation by pondering the articles about its disposition. Furthermore, this may enlighten business stakeholders and policymakers on the substance of digital transformation in the business and economy. This study presents the 20 reviewed literature precisely their basis of the sources of data, geographical settings, statistical treatment employed, distribution of geographical settings of selected studies, the variable usage for digital transformation, its parameters, and the concepts or other variables it is being related with.